2003
DOI: 10.1037/0012-1649.39.4.680
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers' self-regulated compliance to mothers, caregivers, and fathers: Implications for theories of socialization.

Abstract: To compare children's socialized behavior to parents and nonparental agents, this study examined self-regulated compliance to mothers and caregivers--an early form of internalization--in 90 toddlers, half of whom were also observed with fathers. Adults were observed in play, teaching, and discipline sessions with the child and were interviewed on child-rearing philosophies. Child cognition and emotion regulation were assessed, and naturalistic observations were conducted at child-care locations. Mean-level and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
169
2
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(195 citation statements)
references
References 69 publications
13
169
2
11
Order By: Relevance
“…A child' s ability to take the lead in social interactions with caregivers is also thought to contribute to an internal knowledge base that fosters competence in shared activities with a social partner other than the parent. Feldman and Klein (2003) note that support for this notion requires linking early social behavior with caregivers to later social competency with others. Such links have been shown in relation to impulse and behavioral control (Kochanska, 2002), but less frequently related to competencies in shared activities with others.…”
Section: Role Of Early Social Skillsmentioning
confidence: 94%
See 1 more Smart Citation
“…A child' s ability to take the lead in social interactions with caregivers is also thought to contribute to an internal knowledge base that fosters competence in shared activities with a social partner other than the parent. Feldman and Klein (2003) note that support for this notion requires linking early social behavior with caregivers to later social competency with others. Such links have been shown in relation to impulse and behavioral control (Kochanska, 2002), but less frequently related to competencies in shared activities with others.…”
Section: Role Of Early Social Skillsmentioning
confidence: 94%
“…Theories of socialization suggest that children first learn to regulate their behavior when interacting with caregivers and then generalize these skills to interactions with others (Feldman & Klein, 2003;Kochanska & Murray, 2000;Kuczynski & Kochanska, 1995). In the preschool period, this includes the ability to initiate conversation, use language to communicate needs, and successfully cooperate with requests made by caregivers (Landry, Smith, Swank, Assel, & Vellet, 2001).…”
Section: Role Of Early Social Skillsmentioning
confidence: 98%
“…For instance, among researchers focusing on authoritarian or controlling parenting, some found that authoritarian parenting was associated with children's psychological problems [15][16][17], while other researchers found it associated with better psychological adjustment [18][19][20]. Still other researchers found minor or no significant association between authoritarian parenting and children's mental health [21].…”
Section: In Parenting Researchmentioning
confidence: 99%
“…Although there appears to be a major developmental shift in the development of conscience between the ages of 2 and 3, children are already exhibiting these behaviors as young as 2 years of age (Aksan & Kochanska, 2004;Kochanska, 1993;Kochanska, Coy, & Murray, 2001;Kochanska et al, 1994; Previous research suggests that there are two forms of compliance observed in laboratory cleanup tasks: committed or self-regulatory compliance and situational or externally motivated compliance (Feldman & Klein, 2003;Kochanska, Aksan, & Koenig;1995;Parpal & Maccoby 1985). Committed compliance occurs when a child embraces a task wholeheartedly and is eager to accept the parental agenda throughout a given task, whereas situational compliance reflects a child who is generally cooperative, but lacks interest and needs frequent parental prompting to complete a task.…”
Section: Child Compliance and Early Conscience Development As A Predimentioning
confidence: 99%